Сенсорні механізми управління точніснимирухами спортсменів - Anatoly Rovniy; Anatolii Tsos; Vladlena Pasko (Lesya Ukrainka Volyn National University, 2023)
Purpose. To establish the variability of the state of sensory systems and the dependence of control on the precise movements of basketball players from various sensory functions. Investigate. 30 basketball players of the student league at the age of 17-18 years who had a level of preparation of the first sports category and candidate for the master of sports. Result. Established a reliable level of communication between the functions of kinesthetic, visual, vestibular analyzer and the dependence of the accuracy of ball throwing into the basket from individual sensory functions. Conclusion. Results of the conducted researches have determined the sensory regularities of the control by precision throw movements. Studies have established that the accuracy depends on the intensity of the training exercises. Game activity of basketball players occurs at a very high intensity. Therefore for improving the accuracy of throwing the ball requires sensory functions to train with intensity of the exercises, close to the competitive activity.